The moderating role of resilience on the effect of work family conflict and occupational stress on burnout of deployed soldiers at South Africa-Zimbabwe border - Manamela, Dolik Kwena (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.